SISTEM INFORMASI BIMBINGAN BELAJAR PADA BIMBEL LES YUK BERBASIS WEB MENGGUNAKAN MODEL WATERFALL - Yunika Ratna Dian Pratiwi; Nurjaya (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
To reduce these weaknesses, the Yuk Les Tuition Guidance needs to have a system that can make it easier for admins, teachers and students to get information easily and quickly. The methodology used in the design of this information system uses Waterfall, this methodology can be used as a methodology to analyze and design a WEB-Based Tutoring Information System at tutoring Les Yuk. The results of this study indicate that the use of a web-based tutoring information system has accommodated admins in managing administrative data to be more effective, and teachers and students in receiving information both registration and academics are more easily accessible by the internet.